1967
DOI: 10.1152/ajplegacy.1967.212.5.1195
|View full text |Cite
|
Sign up to set email alerts
|

Renin-aldosterone system in endotoxin shock in the dog

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

1971
1971
2006
2006

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 0 publications
2
9
0
Order By: Relevance
“…These results indirectly confirm the findings of White et al (1966) who observed a rise in plasma renin activity 10-20 min after administering endotoxin to dogs, at a time when both renal blood flow and blood pressure had fallen. Central venous pressure was not measured.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These results indirectly confirm the findings of White et al (1966) who observed a rise in plasma renin activity 10-20 min after administering endotoxin to dogs, at a time when both renal blood flow and blood pressure had fallen. Central venous pressure was not measured.…”
Section: Discussionsupporting
confidence: 89%
“…Activation of the kallikrein-kinin system in the rabbit has also been shown (Erdos & Miwa, 1968), and bradykinin levels have been found to be elevated in the monkey (Nies, Forsyth & Williams, 1968). White, Gold & Vaughn (1966) found a rise in plasma renin activity and aldosterone in the dog, the latter presumably being secondary to the generation of angiotensin.…”
Section: Introductionmentioning
confidence: 95%
“…Of 78 articles using flow probes [21, 22, 23, 24, 25, 26, 27, 28, 31, 32, 35, 41, 42, 45, 49, 50, 51, 52, 53, 54, 56, 58, 60, 62, 63, 65, 66, 69, 71, 72, 73, 74, 75, 78, 80, 81, 83, 85, 86, 89, 90, 91, 92, 95, 99, 100, 102, 106, 108, 109, 110, 111, 112, 113, 114, 115, 117, 118, 119, 121, 124, 126, 127, 128, 131, 135, 140, 141, 142, 143, 144, 145, 146, 152, 153, 154, 155], 36 (46.2%) showed a decreased RVR, 11 (14.1%) an unchanged RVR, and 31 (39.7%) a decreased RVR. Of 59 studies using other methods [20, 29, 30, 33, 34, 36, 37, 38, 39, 40, 43, 44, 4...…”
Section: Resultsmentioning
confidence: 99%
“…Among 39 ‘short’ experiments [25, 39, 40, 46, 52, 55, 57, 64, 69, 70, 72, 76, 78, 81, 88, 90, 94, 95, 101, 103, 104, 105, 107, 108, 112, 115, 125, 129, 130, 132, 133, 135, 136, 138, 140, 145, 146, 148,] 14 (35.9%) showed a decreased RVR, 4 (10.3%) no change in RVR, and 21 (53.8%) an increase in RVR. Among the 98 ‘long’ observation time studies [20, 21, 22, 23, 24, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 41, 42, 43, 44, 45, 47, 48, 49, 50, 51, 53, 54, 58, 59, 60, 61, 62, 63, 65, 66, 67, 68, 71, 73, 74, 75, 77, 79, 80, 82, 83, 84, 85, 86, …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation